Quandaries of School Leadership Voices from Principals in the Field (Springer International Publishing, 2018)
This book provides insights into the everyday practices of school leaders as told through the real-life stories of principals. The editors and their contributors blend practice with theory, helping aspiring leaders to discover that school leadership is not simply putting prescribed solutions into action, but a constant encounter with quandaries that demand thinking, responding, and adjusting to the situations at hand. Readers build their capacities to view quandaries from multiple lenses, consider a variety of responses, and draw conclusions based on perspectives that may vary from those initially identified. The chapter authors encourage a sharper self-awareness of what scholars value and envision about education, encouraging them to think about how to navigate decision-making through a variety of theoretical frameworks and practices while balancing their own leadership platform development.